Selenat, selenit ve seleno-DL-metionin'in paracentrotus lividus (Lamarck, 1816) üzerine embriyotoksik ve genotoksik etkilerinin araştırılması - Oral, Rahime (Ege Üniversitesi, 1997)
VI ABSTRACT INVESTIGATION OF EMBRYOTOXIC AND GENOTOXIC EFFECTS OF SELENATE, SELENITE AND SELENO-BL-METHIONINE ON Paracentrotus lividus (LAMARCK, 1816) ORAL, Rahime DSc. in Biology Supervisor : Prof. Dr. Hüseyin Uysal September 1997, 100 pages As a result of antropogenic activities, selenium input to the marine ecosystem has been increased in the recent years. Therefore, especially the river mouths and the coastal areas nearby of industrial discharge outfalls are affected negative way by this element. In this study comparative embryotoxic and genotoxic effects of increasing concentrations (10"7M-3xlO"5M) of selenate (Se04), selenite (SeOa) and seleno-DL-methionine (CsHnNC^Se), were tested on the gametes and embryos of Paracentrotus lividus, living in the littoral areas, which are the dominant echionoid species in the Mediterranean and northeast Atlantic Ocean. Results were evaluated by observing : (a) larval malformations; (b) developmental arrest; (c) embryonic / larval mortality; (d) sperm fertilization success, (e) quantitative and morphologic changes in mitotic activity. Data indicated stimulation in fertilization success of Paracentrotus lividus increase in. the fertilization ratios by about 17 % all tested concentrations without any significant variations of all chemical forms of selenium. However, it was observed significant increases on the pluteus larvae percentages, having especially skeleton malformations on the offspring of the same sperms cultured for 72 hours under optimum conditions compared with control base, and as a result of embryotoxic analysis, the spermiotoxic level were determined to be 10"6 M for selenate, 3xl0"7 M for selenite and 10"7 M for seleno-DL-methionine for this species. But, the embryotoxic level for the same species were determined tovıı be 10"6 M for selenate, 3xl0"7 M for selenite and seleno-DL-methionine. Result of embryological analysis, while low concentrations of all selenium forms generally caused malformations in skeleton systems, it was observed that high ...